Integrating Information and Communication Technology (ICT) in the Farming System for livelihood improvement, “a case of Kieni East constituency, Nyeri County, Kenya - Maina, Paul Mwari (Machakos University, 2019)
In many developing countries, the agriculture sector is dominant in raising incomes among the poor by as much as four times than other sectors. According to the World Bank, 2013, annual report, agriculture reduce poverty, raise incomes and has improved food security for 80% of the world’s poor who depend on farming. The sector realized about 17% of the GDP and 40% of exports. This achievement is attributed to improve agricultural productivity through integration of ICT in the farming system to address SDG number two on zero to hunger. Questionnaires, focus group discussions and interviews were the methods used to collect data. The data was collected from 90 respondents sampled across Kieni East Constituency. The research targeted producer organizations, change teams, extension agents and key stakeholders. The overall objective of the research was to investigate the role of ICT to small holder farmers to harness the benefit of information and communication technologies to maximize returns on agriculture production system. The research examined the role of ICT mainly using market price information through short message service or web portal, open data kit, internet and use of geographical information system in enhancing growth and efficiency in agri-business transactions. The research findings indicated that there is a correlation between increase in information and communication technology and increase in returns on agricultural production system. It also indicated that use of ICT enhanced growth and efficiency in agri-business transactions by empowering the farmer and producer organizations with real time marketing information. The research demonstrated the role of ICT in the systematic dissemination of agricultural information to provide comprehensive, up-to-date and detailed knowledge and information. The research witnessed tremendous advancement in information dissemination among smallholder farmers. Use of ICT in Agricultural extension and education provided an efficient and effective way to reach out to small holder farmers.
Keywords: ICT; Agricultural extension; Agricultural information; Market; Mobile technology